Gorilla beringei (Primates: Hominidae). (1st October 2018) - Canington, Stephanie L
Abstract: Gorilla beringei Matschie, 1903 is a great ape commonly called the eastern gorilla. Highly sexually dimorphic, this diurnal knuckle-walking quadruped is 1 of 2 species of Gorilla, the largest living primates. It is endemic to northwest Rwanda and southwest Uganda as G. b. beringei, and to eastern Democratic Republic of the Congo as G. b. beringei and G. b. graueri . G. beringei is known to both highland and lowland montane forests and subalpine environments, though only G. b. beringei is called the "mountain gorilla." Those inhabiting higher elevations are more folivorous than those at lower elevations. Groups are highly cohesive polygamous social units, varying in size and composition. G. b. beringei and G. b. graueri are both listed as "Critically Endangered" by the International Union for the Conservation of Nature and Natural Resources.